Unmanned Aerial Vehicle Framework for Algae Monitoring - Almeida, Aline Gabriel De; Nascimento, Eduardo Vieira Do; Alvarez, Isaac Gaetani; Kim, Pedro Henrique Corrêa; Rocha, Lidia Gianne Souza Da; Vivaldini, Kelen Cristiane Teixeira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
Several environmental problems requires constant monitoring to ensure that the human interference is not changing the natural habitats. This kind of effort requires many hours of human labor to be performed manually and has a cost associated with it. This work proposes a framework for managing the UAV tasks of creating routes for scanning and sampling algae overgrowth issues in water bodies and makes a comparison between an offline and an online planning strategy that will be tested in a simulated environment.